Does land use influence the local and regional structure of the rotifer assemblage? - dos Santos, Eduardo Fernando [UNESP]; Abra, Juliana; Castilho-Noll, Maria Stela M. [UNESP] (My University, 2021)
The intensification of agriculture has caused severe environmental damage affecting numerous ecosystem services, such as freshwater quality. Understanding and monitoring its impact on the aquatic biota is fundamental to improve the water quality. In this paper, we investigated the influence of environmental condition established by an agropastoral landscape on the local and regional diversity of rotifers. For this, the local and regional diversity were modelled with generalized additive mixed models and canonical correspondence analysis, respectively. Our results indicated that both the local and regional structures of the rotifer assemblage are affected by high nutrient concentrations and other environmental variables. Spatial distance also influences the regional structure, accounting for 23% of the variation in the beta-diversity. The environmental variables are responsible for 9% of the variation in the beta-diversity and the surrounding matrix for 5%. Together, these components and the interactions among them, account for 54% of the regional structure of the rotifer assemblage. Based on our study, we concluded that agriculture lands, primarily citrus crops, adversely influence the rotifer assemblage both locally and regionally. That negative impact, in turn, results in a cascade effect in the aquatic ecosystem, leading mainly to the loss of species-poor taxa.
Keywords: Bottom-up effects; Community structure; Nutrients; Water quality; Zooplankton